2020
DOI: 10.1111/jac.12454
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress effect on polyphenolic content and antioxidant capacity of cowpea pods and seeds

Abstract: Cowpea (Vigna unguiculata L. Walp) is a protein‐rich grain legume with high adaptability to heat and drought and can be consumed during all stages of the plant development. Drought is a severe environmental stress with major impacts on plant development and productivity. This study main objective was to understand the effects of drought stress on polyphenolic content and antioxidant capacity in plant tissue at different stages of cowpea development. Four cowpea genotypes grown until the anthesis under well‐irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
3
10
1
Order By: Relevance
“…Mean antioxidant activity quantified using DPPH asaay declined dramatically under stress. Reduction in antioxidant capacity may be attributed to a decrease in phenol concentration as reported in cow pea (35). Correlation study showed that grain yield was positively related to antioxidant properties in stress.…”
Section: Discussionmentioning
confidence: 70%
“…Mean antioxidant activity quantified using DPPH asaay declined dramatically under stress. Reduction in antioxidant capacity may be attributed to a decrease in phenol concentration as reported in cow pea (35). Correlation study showed that grain yield was positively related to antioxidant properties in stress.…”
Section: Discussionmentioning
confidence: 70%
“…As reactive molecules, ROS oxidize and modify cellular components, thereby causing irreversible DNA damage and even cell death (Huang et al., 2019). Physiological characteristics of plants such as gaseous exchange and water use efficiency are mainly disturbed under drought (Carvalho et al., 2021; Cotrim et al., 2020; Goodarzian‐Ghahfarokhi et al., 2016). Moreover, the integrity of cellular membranes, photosynthetic pigments, osmotic adjustment of osmolytes, and photosynthesis are severely affected by drought stress (Jafari et al., 2019).…”
Section: Impact Of Drought Stress On Plantsmentioning
confidence: 99%
“…It has been a widespread problem that is 2/3rd of the cultivated area worldwide is facing drought stress, which is expected to increase in the coming years due to global warming. Drought stress has deleterious effects on crop growth and productivity through physiological (stomatal closure, root architecture, and so on) and biochemical changes (oxidative stress) and ultimately poses a threat to food security (Aslam et al., 2013; Carvalho et al., 2021). It is highly likely to investigate certain amendments with the potential to enhance crop productivity under drought stress and ultimately leading to food security.…”
Section: Introductionmentioning
confidence: 99%
“…Losses of grain yield/quality from major abiotic stresses such as drought and its combinations with other stresses, cause a significant damage to agriculture, food industry, and economy. Drought, adversely affecting the overall plant metabolism at the physiological, biochemical, and molecular levels, leads to the damages of various cellular compartments, protein degradation, enzyme inactivation, reduced nutrient uptake, transpiration and photosynthesis rates, stomatal closure, growth inhibition, and wilting and drying of plants [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%